Spinal cord stimulator education during pain fellowship: unmet training needs and factors that impact future practice. Issue 3 (March 2019) - Pak, Daniel J; Gruber, Jesse; Deer, Timothy; Provenzano, David; Gulati, Amitabh; Xu, Yifan; Tangel, Virginia; Mehta, Neel
Abstract : Background and objectives: With a growing need for non-opioid chronic pain treatments, pain physicians should understand the proper utilization of neuromodulation therapies to provide the most comprehensive care. We aimed to identify the unmet training needs that deter physicians from using spinal cord stimulation (SCS) devices. Methods: Internet-based surveys were fielded to fellows enrolled in pain fellowships during the 2016–2017 academic year accredited by the Accreditation Council for Graduate Medical Education and past pain fellows identified through pain medicine societies and SCS manufacturers. Results: Current fellows were more likely to have received SCS training during fellowship compared with past fellows (100.0% vs 84.0%), yet there was variability in fellows' SCS experiences with a wide range of trials and implants performed. Forty-six percent of current fellows felt there was an unmet training need regarding SCS. Deficiency in SCS case volume was the most common barrier that was noted (38.5%), followed by lack of SCS curriculum (30.8%) and lack of faculty with SCS expertise (23.1%). Lack of training was a predominant reason for past fellows choosing not to use SCS devices postfellowship. The majority of current and past fellows (79.5% and 55.4%, respectively) strongly supported direct training of fellows by SCS manufacturers. Conclusions: While SCS training during pain fellowship has become more universal, the experiences that fellows receive are highly variable, and most rely on industry-sponsored programs to supplement training deficiencies. Standardization of SCS procedures may also enable less experienced providers to navigate the SCS treatment algorithm.